Stille cross-coupling of a racemic planar-chiral ferrocene and crystallographic trace analysis of catalysis intermediates and by-products - Heinemann, Frank Wilhelm; et al. (Helvetica Chimica Acta, 2007)
A pressure-controlled procedure for the S(N)1 reaction of rac-1-[(dimethylamino)methyl]-2-(tributylstannyl)ferrocene (1) to rac-1-(phthalimidomethyl)-2-(tributylstannyl)ferrocene (2) was developed. Pd-0-Catalyzed Stille coupling of 2 with iodobenzene afforded rac-1-phenyl-2-(N-phthalimidomethyl)-ferrocene (5) in 74% yield; after trace enrichment by crystallization of the combined mother liquors, one single crystal of each, 5, catalysis intermediate trans-iodo(sigma-phenyl)bis(triphenylarsino)palladium(II) (7), trans-diiodobis(triphenylarsino)palladium(II) (8), and rac-2,2'-bis(phthalimidomethyl)-1,1'-biferrocene (9) could be isolated by crystal sorting under a microscope and characterized by X-ray crystal structure analysis. Furthermore, 5 was deprotected to amine (11), which does even survive the Birch reduction to rac-1-(aminomethyl)-2-(cyclohexa-2,5-dienyl)ferrocene (12).